2017
DOI: 10.4103/ijmr.ijmr_199_15
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of celiac disease & type 1 diabetes mellitus in children

Abstract: Background & objectives:Type 1 diabetes mellitus (T1DM) and celiac disease (CD) tend to co-exist due to similar underlying genetic predisposition. Failure to recognize CD in patients with T1DM predisposes them to complications. The present study was aimed to assess children with T1DM for the presence of CD.Methods:This was a retrospective analysis of the records of children with T1DM attending paediatric endocrinology clinic at a tertiary care hospital in north India from January 2006 to May 2014. All children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
3
15
0
1
Order By: Relevance
“…Most screening studies on the prevalence of CD include diabetic children and adolescents, persons with thyroid disorders, persons with Down syndrome and those with close relations with CD (some of these are given by country in Table 3 [52-67]). The high prevalence of CD among patients with type 1 diabetes mellitus (up to 13.5%) is probably due to clinical and pathogenic overlap [68], and symptoms are often modest or absent.…”
Section: Screening Strategies In Paediatric Populationsmentioning
confidence: 99%
“…Most screening studies on the prevalence of CD include diabetic children and adolescents, persons with thyroid disorders, persons with Down syndrome and those with close relations with CD (some of these are given by country in Table 3 [52-67]). The high prevalence of CD among patients with type 1 diabetes mellitus (up to 13.5%) is probably due to clinical and pathogenic overlap [68], and symptoms are often modest or absent.…”
Section: Screening Strategies In Paediatric Populationsmentioning
confidence: 99%
“…Studies done earlier from this country had shown a 34.1% prevalence of celiac disease associated anti-tissue transglutaminase IgA antibody in subjects with T1DM. [ 14 ] Another study from the country had shown a prevalence of 11.1% of celiac disease associated autoantibody in T1DM. [ 15 ] We appreciate that, before declaring a patient to be negative for celiac antibody by IgA, anti-tTG, total IgA deficiency must be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In Indian patients with T1DM, a variable frequency of seropositivity of tTG antibody and CD has been reported. The frequency was reported to be higher in patients of north Indian origin (tTG antibody 11-34%; CD 3.8-13.5%) compared with a study from southern India (tTG antibody 5%)121314. The reason for this is not clear, but it may be due to the differences in frequency of genetic susceptibility loci or environmental factors such as the age of initiating gluten-containing foods in infancy.…”
mentioning
confidence: 84%